TAFSIR FITRI IMAM KHOMENI - Ammar Fauzi (Sekolah Tinggi Agama Islam (STAI) Sadra, 2016)
This paper is intended to identify the axis of the Sufism tendency of Imam Khomeini and his interpretation of irfani-isyari (legal-gnostical). In view of Imam Khomeini, inborn nature (fitrah) is considered as the main basic for self-knowledge (ma’rifat alnafs). According to him, irfan (gnostic) basically is the exegesis itself. And if the soul of irfan is fitrah and irfan is a form of Qur’anic exegesis, then the fitrah is also part of the core layer of gnostic interpretation. Through the observation of his works is enough to reveal the fact one of the layers of his intellectual personality as an interpreter who greatly accentuate spiritual revelation. He believes that irfan is inseparable from interpretation, because essentially, irfan is the interpretation itself. The naming of this irfan model is initiated from his mystical letters. It is known that all interpretations of Sufism and Imam Khomeini’s essence are essentially interpretations and explanations of verses of the Qur’an and hadith (tradition).